2019
DOI: 10.1116/1.5122776
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic ellipsometry and optical spectroscopy of plasmons in classic 3D topological insulators

Abstract: Narrow bandgap Bi2Se3, Bi2Te3, and Sb2Te3, commonly referred to as classic 3D topological insulators, were studied at room temperature by spectroscopic ellipsometry and optical reflection spectroscopy over the mid-IR–near-infrared photon energy range. Complementarily, Hall measurements were performed. Plasmons in optical loss function and reflection coefficient were identified. The conventional approach based on the high frequency dielectric constant was shown to work well in the description of plasmons in Bi2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
6
0
3
Order By: Relevance
“…the partial molar Gibbs free energy, enthalpy, and entropy of bismuth in the alloys were calculated (Table 4). (11) the standard thermodynamic functions of the formation of Bi 2 Te 3 and Bi 4 Te 5 were calculated. In relations (8) and (9) Z  G or H. For the thermodynamic calculations, we used the literature data [29] on the standard entropies of elementary bismuth (56.7 ± 0.5 Jmol -1 К -1 ) and tellurium (49.5±0.2 Jmol -1 К -1 ).…”
Section: Fig 1 Powder X-ray Of a Two-phase Alloy Bi 4 Te 5 +Bi 2 Tementioning
confidence: 99%
See 1 more Smart Citation
“…the partial molar Gibbs free energy, enthalpy, and entropy of bismuth in the alloys were calculated (Table 4). (11) the standard thermodynamic functions of the formation of Bi 2 Te 3 and Bi 4 Te 5 were calculated. In relations (8) and (9) Z  G or H. For the thermodynamic calculations, we used the literature data [29] on the standard entropies of elementary bismuth (56.7 ± 0.5 Jmol -1 К -1 ) and tellurium (49.5±0.2 Jmol -1 К -1 ).…”
Section: Fig 1 Powder X-ray Of a Two-phase Alloy Bi 4 Te 5 +Bi 2 Tementioning
confidence: 99%
“…Bismuth tellurides, especially Bi 2 Тe 3 , phases, and composites based on it have long been in the field of view of researchers as valuable thermoelectric materials [1][2][3]. After the discovery of a special quantum state of mattera topological insulator (TI) [4], it was found that Bi2Te3 and many other layered compounds of tetradimite-like structures are TI which are rather promising for their varied applications [5][6][7][8][9][10][11]. In particular, the unique optical properties make them promising for the use in broadband optoelectronics as photodetectors [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ранее в литературе было показано, что частоты возбуждения ППР в Bi 2 Se 3 и Sb 2 Te 3 приходятся на ИК область, тем самым исследование Bi 2 Se 3 и Sb 2 Te 3 в качестве плазмонных материалов становится очень перспективным направлением. Плазменная частота зависит от концентрации свободных носителей заряда, эта зависимость описывается известной формулой [7]:…”
Section: Introductionunclassified
“…где ω -частота электромагнитной волны, ε a -диэлектрическая постоянная призмы, c -скорость света и θугол падения волны. Ранее публиковались работы по наблюдению плазмонов в данных соединениях и в других структурах типа тетрадимит [7,9,10], но сведений о ППР и его применении для ИК плазмонных устройств и исследования свойств плазмона в литературе нет. В данной работе это выполнено впервые.…”
Section: Introductionunclassified
“…The above compounds also apply to materials promising for the specified area [9][10][11]. MnBi 2 Te 4 (the first antiferromagnetic topological insulator) MnBi 4 Te 7 and MnBi 6 Te 10 compounds were described in papers [12][13][14][15] publicshed recently.…”
Section: Introductionmentioning
confidence: 99%